Exploring the vagus nerve and the inflammatory reflex for therapeutic benefit in chronic spinal cord injury. Issue 2 (31st January 2022) - Bloom, Ona; Tracey, Kevin J.; Pavlov, Valentin A.
Abstract : Purpose of review: To describe features and implications of chronic systemic inflammation in individuals with spinal cord injury (SCI) and to summarize the growing therapeutic possibilities to explore the vagus nerve-mediated inflammatory reflex in this context. Recent findings: The discovery of the inflammatory reflex provides a rationale to explore neuromodulation modalities, that is, electrical vagus nerve stimulation and pharmacological cholinergic modalities to regulate inflammation after SCI. Summary: Inflammation in individuals with SCI may negatively impact functional recovery and medical consequences after SCI. Exploring the potential of the vagus nerve-based inflammatory reflex to restore autonomic regulation and control inflammation may provide a novel approach for functional improvement in SCI.